Grouping of Performance Effectiveness Assessment of Forest Management Units in North Sumatra Province - Siregar, Tumpak; OK Hasnanda Syahputra; Siti Latifah (Journal of Sylva Indonesiana, 2025)
Forest Management Units (FMU) are established to realize the effective and sustainable management of forests and other management plans, including organization, implementation management, as well as control and supervision. The management of forests by FMU is closely tied to the role of existing human resources, both qualitatively and quantitatively, as well as the rate of deforestation. To understand the extent of FMU's performance success, an instrument in the form of a Performance Assessment is needed as an evaluation tool for achieving forest management, one of which is by using the questionnaire based on the Technical Guidelines for Assessing Effective Forest Management Institutions in Supporting Independent Communities and Sustainable Forests from the Director of Forest Utilization Planning Development. The performance assessment variables are then processed using cluster analysis to obtain groupings of FMUs in North Sumatra Province based on clusters and the average effectiveness value of FMUs. The research results show that there are 3 Clusters with details for Cluster I consisting of 7 (seven) Units, Cluster II consisting of 11 (eleven) Units, and Cluster III consisting of 15 (fifteen) Units. The characteristics obtained in Cluster 1 indicate that all variables are above the population average, which represents Effective FMUs